Microwave-assisted solvothermal preparation of Zr-BDC for modification of proton exchange membranes made of SPEEK/PBI blends - da Trindade, L. G. [UNESP]; Zanchet, L.; Dreon, R.; Souza, J. C.; Assis, M.; Longo, E.; Martini, E. M.A.; Chiquito, A. J.; Pontes, F. M. [UNESP] (Springer Nature, 2020)
Sulfonated poly(ether ether ketone)/polybenzimidazole (SPEEK/PBI) blends were made with different quantities of metal organic (Zr-BDC) synthesized by microwave-assisted solvothermal method. These composite membranes had their synthesis and characterization explored to verify their application as novel proton exchange membranes (PEM). The Zr-BDC influence on the composite membranes was evaluated through the morphology analysis and thermal and chemical stability investigation. Thermal and swelling analysis evidenced stability of the blends provided by the Zr-BDC presence, and also it improved their proton conductivity. The incorporation of 12.5 wt% Zr-BDC in SPEEK/PBI blends resulted in high proton conductivity in two different PBI concentrations analyzed at 80 °C. This behavior evidences that in the SPEEK/PBI/Zr-BDC system the breaking and forming process of hydrogen bonds may have some positive effects in the increment of the proton conductivity. The data suggest that the SPEEK/PBI (20 wt%)/Zr-BDC (12.5 wt%) membrane is a suitable candidate for use in proton exchange membrane fuel cells.